Project design for geomatics engineers and surveyors - Ogaja, Clement A.; Adero, Nashon Juma; Koome, Derrick (CRC Press, 2023)
"Project Design for Geomatics Engineers and Surveyors, Second Edition", continues to focus on the key components and aspects of project design for geomatics and land surveying projects with the goal of helping readers navigate the priority issues when planning new projects. The second edition includes new materials on surveying and UAV, and it is thoroughly updated to keep current with the recent technology and terminology. The two new chapters capture new developments in the rapidly emerging use of remote sensing and GIS in aerial surveys, mapping, and imaging for small-to-medium scale projects, as well as modern practices and experiences in engineering surveying."